Study of the Effect of Grain Angle on the Compressive Strength of Red Meranti Timber (Shorea spp.) - Pranata, Yosafat Aji; Kristianto, Anang; Novi, Novi (Wood Research Journal, 2024)
The compressive strength of timber is the main parameter in designing truss system, for instance timber bridges, building roof, or column in buildings. In term of design of compression structural components according to the SNI 7973:2013, the corrected compression design value is a calculation of compressive strength parameters and correction factors, for example, wet service factors, temperature factors, column stability factors, and others. Timber as an orthotropic material has three main directions, therefore the angle of the timber grain has an influence on compressive strength. This research aims to study the effect of timber grain’s angle on the compressive strength of Red Meranti wood (Shorea spp.) and develop an empirical equation to calculate the compressive strength of timber with the influence of the wood grain’s angle. The test specimens were made based on the primary method reference for compression test namely 50mm x 50mm x 200mm (parallel to the grain type), according to ASTM D143-22 for test specimens with variations in fiber direction, namely 0°, 10°, 20° and 30°. Meanwhile, test objects with variations in fiber direction, namely 60°, 70°, 80° and 90°, were made the sizes of 50mm x 50mm x 150mm (perpendicular to the grain type). Testings were carried out using a Universal Testing Machine with test speed according to ASTM D143-22. All test objects were made in dry conditions (moisture content ranging from 14% to 16%). The conclusion obtained from this research are an empirical equation for calculating the compressive strength of Red Meranti timber with a predictor is the timber grain’s angle, which are FCY = 14.01 – 0.119θ + 0.000042θ2 (in term of yield of proportional point) and FCU = 29.82 – 0.417θ + 0.0018θ2 (in term of peak or ultimate point). This equation provides benefits for academics and practitioners, especially in designing compression structural components especially with compression value as the main parameter.